Comparison of cytotoxicity of IQOS aerosols to smoke from Marlboro Red and 3R4F reference cigarettes. (December 2019) - Davis, Barbara; To, Vivian; Talbot, Prue
Abstract: This study compared the cytotoxicity of IQOS aerosols to smoke from Marlboro Red (MR) and 3R4F reference cigarettes. Aerosol/smoke solutions were tested as the gas vapor phase (GVP), particulate phase (total particulate matter or TPM), or whole aerosol/smoke (WA), the latter being what smokers actually inhale. Cytotoxicities were evaluated using the LDH, MTT and neutral red uptake (NRU) assays in conjunction with eight different cell types, mainly from the respiratory system. Most test solutions did not compromise the plasma membranes of cells (LDH). However, mitochondrial activity (MTT) and dye uptake/lysosomal activity (NRU) were equally depressed by IOQS aerosols and cigarette smoke solutions at the high concentrations. Our NRU data with mouse NIH/3T3 transformed fibroblasts were similar to those previously reported by the IQOS manufacturer and showed little cytotoxicity in the NRU assay. In both studies with NIH/3T3 cells, the results were significantly different from 3RF4 cigarette smoke, suggesting reduced toxicity with IQOS. However, by expanding evaluations to a broader spectrum of cells that included respiratory system cells and by including higher concentrations of GVP, as well as WA, cytotoxicity equivalent to that of Marlboro Red and 3R4F cigarettes was frequently observed with IQOS aerosols in the MTT and NRU assays. Highlights: Cytotoxicities of vapor, particulate and whole IQOS aerosols were compared for eight cell types. IQOS aerosols did not produce cytotoxicity in the NRU assay with mouse 3T3 fibroblasts. However, human cells from the respiratory system were adversely affected by IQOS aerosols The sensitivity of six respiratory system cells to IQOS aerosols varied with cell type. In some cases, IQOS aerosol was as cytotoxic as smoke from commercial and research cigarettes.